2017
DOI: 10.1016/j.socscimed.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing hypothetical willingness from behavioral intentions to initiate HIV pre-exposure prophylaxis (PrEP): Findings from a large cohort of gay and bisexual men in the U.S.

Abstract: Rationale Much of the data on the acceptability of HIV Pre-Exposure Prophylaxis (PrEP) is based on willingness to take PrEP (i.e., hypothetical receptivity) rather than actual intentions (i.e., planned behavioral action) to do so. Objective We sought to examine differences between hypothetical willingness and behavioral intentions to begin PrEP in a national sample of gay and bisexual men (GBM) across the U.S. Methods We utilized data collected in 2015 to examine differences between those Unwilling (42.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 43 publications
8
66
2
Order By: Relevance
“…Recent research has identified inconsistencies in hypothetical willingness and actual intentions in PrEP uptake, highlighting limits inherent in acceptability research. 36 All MSM in this study were currently taking daily oral PrEP, demonstrating an established willingness to take this medication. By asking participants to rank each formulation and indicate whether or not they prefer each form to daily oral PrEP, our measures of preference may circumvent the ''willingness'' versus ''intentions'' disconnect.…”
Section: Discussionmentioning
confidence: 92%
“…Recent research has identified inconsistencies in hypothetical willingness and actual intentions in PrEP uptake, highlighting limits inherent in acceptability research. 36 All MSM in this study were currently taking daily oral PrEP, demonstrating an established willingness to take this medication. By asking participants to rank each formulation and indicate whether or not they prefer each form to daily oral PrEP, our measures of preference may circumvent the ''willingness'' versus ''intentions'' disconnect.…”
Section: Discussionmentioning
confidence: 92%
“…In conceptualizing the transition from Precontemplation through Contemplation and PrEParation, the distinction between willingness versus intentions or opportunity emerged as a critical aspect of the Motivational PrEP Cascade based on earlier work [27]. Not all GBM who were open (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 301 GBM who completed both processes in the Contemplation stage (meaning they were willing to take PrEP and believed they were an appropriate candidate), the majority (81%) reported having access to a PrEP provider, though fewer (57.5%) reported intentions to begin PrEP. The incorporation of the motivational concept of “intentions” in this stage identifies a potentially critical point of intervention to enhance PrEP uptake [27]. Providers could consider a decisional balance exercise of the pros and cons of PrEP uptake [28, 29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research generally indicates a high degree of ambivalence about PrEP among men, with one recent study revealing almost equal numbers of men unwilling (42%) and willing (41%) to take PrEP (Rendina et al, 2017). In a survey of nearly 1000 gay and bisexual men across the U.S., Parsons et al (2017) found that 53% of men who met the criteria established by the CDC were unwilling to take PrEP or did not believe they were appropriate candidates.…”
Section: Prep Public Health and Sexual Culturementioning
confidence: 99%